INTERNALISASI NILAI KERJASAMA PADA KULIAH KERJA MAHASISWA BERBASIS PARTICIPATORY ACTION RESEARCH SEBAGAI UPAYA MEWUJUDKAN KEPEDULIAN SOSIAL - Deden Sudirman (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This research evelop teamwork internalization model through internship which is based on Participatory Action Research. Participants are students at IAIN Syekh Nurjati Cirebon involved in qualitative deasign. Result shows that internship based on Participatory Action Research has been conducted in group from preparation, implementation, until evaluation. Internalization process of cooperative values in internship occurs when the students have dinamic, participative and collaborative learning making process in making Mapping, Seasonal Calender, Diagram Venn, Time Line, Trend and Change, Matrix ranking and flowchart. Partisipative model can be developed on purpose, content, method, and evaluation